2014
DOI: 10.1134/s0006297914130021
|View full text |Cite
|
Sign up to set email alerts
|

Functions of noncoding sequences in mammalian genomes

Abstract: Most of the mammalian genome consists of nucleotide sequences not coding for proteins. Exons of genes make up only 3% of the human genome, while the significance of most other sequences remains unknown. Recent genome studies with high-throughput methods demonstrate that the so-called noncoding part of the genome may perform important functions. This hypothesis is supported by three groups of experimental data: 1) approximately 10% of the sequences, most of which are located in noncoding parts of the genome, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 220 publications
0
40
0
1
Order By: Relevance
“…The rs480414 G/A SNP is located in the intron of the DDAH1 gene on chromosome 1p22. Although the intron is a noncoding region, recent studies have shown that mutations in noncoding parts of the genome can be associated with disease progression (27). Introns can work to positively regulate gene expression by stimulating mRNA accumulation through a process known as intron-mediated enhancement (28).…”
Section: Discussionmentioning
confidence: 99%
“…The rs480414 G/A SNP is located in the intron of the DDAH1 gene on chromosome 1p22. Although the intron is a noncoding region, recent studies have shown that mutations in noncoding parts of the genome can be associated with disease progression (27). Introns can work to positively regulate gene expression by stimulating mRNA accumulation through a process known as intron-mediated enhancement (28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sequences of introns do not represent junk DNA, but actually play a key role in gene expression and regulation [14]. Thus, whether the expression of these genes is disturbed will form the basis of subsequent studies from our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The typing strategy described here utilizes long-range PCR to amplify full-length sequences of class I genes (HLA-A, B, C), and uninterrupted sequences from exon 2 to beginning of exon 4 of class II (HLA-DRB1 and DQB1), thereby providing valuable intron information involving previously unmapped regions. Intron sequences constitute approximately 30% of the human genome [30]; however, the function of introns is not completely understood. Recent NGS studies have shown that noncoding RNAs (ncRNAs), including miRNA, siRNA, long noncoding RNAs (lncRNAs) and small nucleolar RNAs (snoRNAs) found in intron regions of the human genome may play an important role in regulating gene expression [31,32].…”
Section: Discussionmentioning
confidence: 99%